STABILIZATION OF THE WEATHERED SOILS AND FORMATION OF PERMANENT GRASS GREEN COVER BY CRYOSTRUCTURING - K, Altunina L; I, Svarovskaya L; T, Gan-Erdene; S, Fufaeva M; A, Filatov D; Ch, Batjargal; M, Bayarjargal (Proceedings of the Mongolian Academy of Sciences, 2017)
A new chemical-biological method of preventing soil erosion using cryogel in combination with perennial grasses is proposed. The cryogel is shown not to have negative impact on aboriginal soil microflora. On the one hand the cryogel polymer matrix in the soil is strong enough to withstand the effects of erosion but on the other hand it is quite elastic, so it will not hinder plant growth. The seeds germinated through the cryogel layer form a stable green cover. Cryogels are harmless to humans and environmentally friendly.